Short sea migration and precocious maturation in reared Atlantic salmon post-smolts in the northern Baltic Sea. (24th November 2017) - Orell, Panu; Erkinaro, Jaakko; Kiljunen, Mikko; Torniainen, Jyrki; Sutela, Tapio; Jaukkuri, Mikko; Mäki-Petäys, Aki
Abstract: Atlantic salmon ( Salmo salar L.) display significant variation in life history traits, including migration patterns and age at maturity. Hatchery rearing has been shown to affect the life history, and rearing-induced changes may include unfavourable consequences, e.g. shortened sea migration period and smaller size at maturity. We report on a new phenomenon of life history of reared Atlantic salmon in the Baltic Sea area: small-sized salmon returning to freshwater only a few months after release as smolts. These "one-sea-summer (1SS)" salmon were ca. 35 cm in length and weighed ca. 400 g, being clearly larger than smolts, but substantially smaller than one-sea-winter (1SW) salmon from the same cohorts. Almost all 1SS salmon were mature males and, at release, had been longer than the overall mean. Stable isotope analysis suggested that the 1SS salmon had been feeding in different sea areas than 1SW and multi-sea-winter salmon, likely in nearby Bothnian Bay, which is typically not a salmon feeding area. If an increasing proportion of the released salmon are not undertaking a normal marine migration (≥1SW) and are returning to estuaries and rivers as 1SS fish, the success and profitability of the reared salmon releases will decline even more than the reduced post-smolt survival is suggesting. We suggest that alternative rearing practices (e.g. enriched rearing environments and advanced diets) should be considered in hatchery production for shaping the reared smolts towards a closer resemblance to wild smolts.